2015
DOI: 10.1002/nbm.3354
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time measurement of hyperpolarized lactate production and efflux as a biomarker of tumor aggressiveness in an MR compatible 3D cell culture bioreactor

Abstract: We have developed a 3D cell/tissue culture bioreactor compatible with hyperpolarized (HP) 13C MR and interrogated HP [1-13C] lactate production and efflux in human renal cell carcinoma (RCC) cells. This platform is capable of resolving intracellular and extracellular HP lactate pools, allowing the kinetic measurement of lactate production and efflux in the context of cancer aggressiveness and response to therapy. HP 13C MR studies were performed on 3 immortalized human renal cell lines: HK2, a normal renal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 58 publications
3
57
0
Order By: Relevance
“…UOK262 cells were used for this experiment because they are known to transport relatively large amounts of lactate out into the extracellular environment [7,8]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…UOK262 cells were used for this experiment because they are known to transport relatively large amounts of lactate out into the extracellular environment [7,8]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with a prior published MR compatible cell culture bioreactor study of UOK262 cells, in which flow-rate modulations in the bioreactor demonstrated that hyperpolarized 13 C lactate was transported out of the cell and washed-away during the time frame of the hyperpolarized MR study [7]. Furthermore, a recent publication studying UOK262 cells in a 5 mm MR compatible bioreactor, which enabled a spectral line-width narrow enough for the separation of the intra- and extracellular hyperpolarized 13 C lactate peaks, showed that when subjected to DIDS inhibition, the ratio of intra- to extracellular lactate increased by 1.64-fold [8]. This study showed a 2.35-fold increase in the intra- to extracellular lactate ratio with DIDS inhibition (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal cell carcinomas (RCCs) are a broad group of tumors affecting the kidney that have been studied in some detail using hyperpolarized 13 C. In vitro HP [1- 13 C]pyruvate studies of two different RCC cell lines (UOK262 and UMRC6) and healthy proximal tubule epithelial (HK-2) cells have shown that the observed pyruvate to lactate ratio and the ratio of HP intracellular lactate to extracellular lactate (efflux ratio) can be used to distinguish the three different cell lines from each other [262,263]. Furthermore, the HP lactate efflux ratio strongly correlates with MCT4 mRNA expression, suggesting its potential use as a biomarker for differential diagnosis of RCCs.…”
Section: Hyperpolarized Studies By Organ Systemmentioning
confidence: 99%